(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2024)
The present study deals with the way in which the modulation of the temporal effects of the decision in constitutionality control presents itself as a safeguard of legal certainty, specifically considering the new hypothesis of rescission action, and its differentiated statute of limitations, provided for in the current Code of Civil Procedure, specifically in articles 525, § 15 and 535, § 8. Initially, legal security and its scope were addressed, emphasizing its importance as a fundamental right, even exposing the special emphasis that the current CPC gave to the institute, aiming to guarantee it and make it effective. Then, the aspects of the temporal modulation of the effects of the decision in constitutionality control and its importance as a means of guaranteeing legal certainty are exposed, also highlighting the provisions of the CPC on the subject. Furthermore, the study of the hypothesis of a rescission action against an unappealable decision based on a rule later held by the STF as unconstitutional, was addressed, with special emphasis on the statute of limitations of the aforementioned action and the understanding of the consolidated STF in a direction contrary to that provided for in the CPC, while the CPC was still in the vacatio legis period. Finally, the relevance and importance of the modulation of the effects as an instrument guaranteeing legal certainty is analyzed, in view of the aforementioned termination action and, especially, due to its statute of limitations differentiated from other termination actions.